Influence of Intraoperative Hemodynamic Stability on Wound Dehiscence in Patients Receiving General Anesthesia for Major Abdominal Surgery - Sarah Nadia Jamal, Neelam Noreen, Qamber Ali Laghari, Rana Shoaib Aslam, Ratan Kumar Ramani, Muhammad Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Wound dehiscence, the separation of a surgical incision at the fascial level, remains a serious complication following major abdominal operations. Inadequate tissue perfusion due to intraoperative hemodynamic instability may impair collagen synthesis and increase the risk of fascial separation, yet prospective data in this setting are limited. Objective: To determine whether intraoperative deviations in mean arterial pressure (MAP) and heart rate (HR) beyond 20 % of baseline values are associated with higher rates of wound dehiscence in patients undergoing elective major abdominal surgery under general anesthesia. Methods: This prospective observational study enrolled 100 patients aged 18–65 years undergoing elective major abdominal surgery at Dr. Ruth K.M. Pfau Civil Hospital Karachi and Bolan Medical Complex Hospital Quetta from January 2022 to January 2023. Hemodynamic stability was defined as maintenance of MAP and HR within ± 20 % of baseline throughout the procedure. Episodes exceeding these thresholds for more than ten consecutive minutes despite initial corrective measures (fluid bolus, anesthetic adjustment, vasoactive support) were classified as “intraoperative hemodynamic instability.” Patients were monitored for 30 days postoperatively for wound dehiscence, defined as fascial separation requiring manual or surgical intervention. Data were analyzed using SPSS version 25, with chi-square tests for categorical comparisons and multivariate logistic regression to identify independent predictors of dehiscence (p < 0.05 significant). Results: Sixty-five patients (65 %) maintained intraoperative hemodynamic stability, while 35 (35 %) experienced instability. Overall wound dehiscence occurred in 10/100 (10 %) patients: 2/65 (3.1 %) in the stable group versus 8/35 (22.9 %) in the unstable group (p < 0.001). Multivariate analysis identified intraoperative hemodynamic instability as an independent predictor of dehiscence (odds ratio = 4.5; 95 % CI: 1.6–12.6; p = 0.003), after adjustment for age, BMI, diabetes, and duration of surgery. Conclusion: Intraoperative hemodynamic instability defined as sustained deviations in MAP and HR beyond 20 % of baseline significantly increases the risk of postoperative wound dehiscence in major abdominal surgery. Vigilant hemodynamic management may reduce this complication. Keywords: Wound dehiscence; intraoperative hemodynamic instability; major abdominal surgery; general anesthesia; fascial separation.